METROPOLlZAÇÃO NA ILHA OE SÃO LUIS E SEUS IMPACTOS SANITÁRIOS E AMBIENTAIS - Lúcio Antônio Alves de Macêdo (Universidade Federal do Maranhão, 2012)
The paper presents aspects 01 the Environmental Sanitation considered on the island 01 Maranhão, lrom a historical perspective, restoring the role 01 sanitation in improving the quality 01 lile and highlighting the low leveis 01 coverage 01 water supply (56%) and sanitation (12%), and the precariousness 01 the disposal 01 solid waste in the municipalities 01 São Luis, Paço do Lumiar, Raposa and São José de Ribamar. ln particular there is no more available land lar construction 01 landlills, because 01 environmental implications in areas 01 watershed protection. As a result 01 the studies showed that water pollution in major rivers 01 the island with the pollution load 0160 ton / day, committing the multiple uses 01 the river Anil, Bacanga, Patience and Tibiri, as well as high rates 01 inlectious diseases and child mortality the precariousness 01 Sanitation problems associated with the generation 01 700 t / d 01 waste. ln conclusion the study shows the need lar the implementation 01 environmental planning, ordering the use 01 space and adopting techniques 01 control and environmental health lar the population.